Designing Tubular Architectures Composed of Hollow N‐Doped Carbon Polyhedrons for Improved Supercapacitance. Issue 16 (21st July 2021) - Xu, Hai; Yao, Zhenjie; Gong, Yujiao; Dai, Henghan; Yu, Chenyang; Qin, Gang; Zhou, Jinyuan; Chen, Qiang; Liu, Xiang; Sun, Gengzhi
Abstract: Despite great efforts that have been made to develop high performance carbonaceous materials via structure design for charge storage applications, constructing tubular architectures composed of hierarchically nanoscale building units is challenging due to the lack of suitable synthetic method. Herein, using zeolitic imidazolate framework‐8 (ZIF‐8) as the self‐template and electrospun polyacrylonitrile (PAN) nanofibers as the sacrificial core, hierarchically tubular architectures composed of hollow N‐doped carbon polyhedrons (T‐HNCPs) are successfully obtained. Due to its unique structural characteristics and the merit of N‐doping, the as‐prepared T‐HNCPs electrode with much open structure (average pore size of ≈2.38 nm and specific surface area of 1302.5 m 2 g −1 ) exhibits improved specific gravimetric capacitances of 351.2 and 230.4 F g −1 at 1 and 20 A g −1 (corresponding to 65.6% retention), respectively, together with outstanding charge/discharge stability. Abstract : Hierarchically tubular architectures composed of hollow N‐doped carbon polyhedrons (T‐HNCPs) using zeolitic imidazolate framework‐8 (ZIF‐8) as the self‐templates and electrospun polyacrylonitrile nanofibers as the sacrificial core are fabricated. Due to its unique structural characteristics and the merit of N‐doping, the as‐prepared T‐HNCPs electrode exhibits improved specific gravimetric capacitances together with outstanding charge/discharge stability.